Paradigm Menemukan Kekatolikan Baru: Telaah Pemikiran Ilia Delio tentang Teologi, Sains, dan Teknologi: Discovering a New Catholicism: A Study of Ilia Delio’s Thought on Theology, Science, and Technology - Triesadi, Bernardus Andriananta Hadityo; Atawolo, Andreas Bernadinus (FOCUS, 2025)
This study explores Ilia Delio’s thought on a new paradigm of “catholicity” within the context of dialogue between faith and science. This topic is significant because the Catholic Church is frequently challenged to reassess the relevance of its teachings amid the rapid advancement of scientific knowledge and the global ecological crisis. The research employs a qualitative method with a hermeneutic approach and literature review of Delio’s works. The main findings indicate that “catholicity” should not be understood merely as an institution or doctrinal system, but as a spiritual consciousness that unites all of creation in the love of God. The holistic dimension highlighted includes the interconnectedness of the universe, humanity, Christ, and the Church as part of a cosmic evolutionary process directed toward unity. The implications of this thought are relevant for the development of contextual theology, especially in addressing technological and ecological challenges in a more inclusive and sustainable way. This study offers added value through a systematic synthesis of Delio’s ideas and their potential application in renewing theological understandings of the identity and mission of the Catholic Church in the contemporary era.